A STING inhibitor suppresses EBV‐induced B cell transformation and lymphomagenesis. Issue 12 (11th October 2021) - Miyagi, Shouhei; Watanabe, Takahiro; Hara, Yuya; Arata, Masataka; Uddin, Md. Kamal; Mantoku, Keisuke; Sago, Ken; Yanagi, Yusuke; Suzuki, Takeshi; Masud, H. M. Abdullah Al; Kawada, Jun‐ichi; Nakamura, Shigeo; et al.
Abstract: Epstein‐Barr virus‐associated lymphoproliferative disease (EBV‐LPD) is frequently fatal. Innate immunity plays a key role in protecting against pathogens and cancers. The stimulator of interferon genes (STING) is regarded as a key adaptor protein allowing DNA sensors recognizing exogenous cytosolic DNA to activate the type I interferon signaling cascade. In terms of EBV tumorigenicity, the role of STING remains elusive. Here we showed that treatment with the STING inhibitor, C‐176, suppressed EBV‐induced transformation in peripheral blood mononuclear cells. In an EBV‐LPD mouse model, C‐176 treatment also inhibited tumor formation and prolonged survival. Treatment with B cells alone did not affect EBV transformation, but suppression of EBV‐induced transformation was observed in the presence of T cells. Even without direct B cell‐T cell contact in a transwell system, the inhibitor reduced the transformation activity, indicating that intercellular communication by humoral factors was critical to prevent EBV‐induced transformation. These findings suggest that inhibition of STING signaling pathway with C‐176 could be a new therapeutic target of EBV‐LPD. Abstract : Treatment with STING inhibitor, C‐176, suppressed the tumor formation in a mouse model of EBV LPDs. Although inhibitor treatment with B cells in vitro alone did not affect EBV transformation, the suppression of EBV‐induced transformation was observed in the presence of T cells